2006
DOI: 10.1038/sj.emboj.7601228
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation and MAPK phosphorylation cooperate to regulate the degradation of active GATA-1

Abstract: Regulation of transcription requires mechanisms to both activate and terminate transcription factor activity. GATA-1 is a key haemopoietic transcription factor whose activity is increased by acetylation. We show here that acetylated GATA-1 is targeted for degradation via the ubiquitin/proteasome pathway. Acetylation positively signals ubiquitination, suggesting that activation by acetylation simultaneously marks GATA-1 for degradation. Promoter-specific MAPK phosphorylation then cooperates with acetylation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 35 publications
5
75
0
3
Order By: Relevance
“…Previous reports have shown that acetylation of nonhistone proteins may be linked to regulation of their stability (Hernandez-Hernandez et al, 2006;Leduc et al, 2006;Mateo et al, 2009 (Figure 2c). This observation implies that N3 IC is a substrate of HAT-dependent acetylation.…”
Section: Tsa Treatment Regulates Notch3 Signalingmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous reports have shown that acetylation of nonhistone proteins may be linked to regulation of their stability (Hernandez-Hernandez et al, 2006;Leduc et al, 2006;Mateo et al, 2009 (Figure 2c). This observation implies that N3 IC is a substrate of HAT-dependent acetylation.…”
Section: Tsa Treatment Regulates Notch3 Signalingmentioning
confidence: 73%
“…Protein acetylation has been reported to prime subsequent ubiquitin-dependent stability of target proteins (Hernandez-Hernandez et al, 2006;Leduc et al, 2006). Although we and others suggested that proteasomal degradation of Notch intracellular domain (N IC ) may be required for repressing Notch signaling, the underlying mechanisms are still to be clarified.…”
Section: Acetylation Regulates Notch3 Ubiquitination Proteasomal Degmentioning
confidence: 95%
“…Although serine phosphorylation of GATA-1 has been reported, its role on GATA-1 function remains unclear. [39][40][41] These observations indicate that study of the functional relevance of GATA-1 tyrosine phosphorylation is warranted in AMKL. …”
Section: Discussionmentioning
confidence: 99%
“…The function of GATA1 can be regulated by an array of posttranslational modifications, including phosphorylation and acetylation as well as SUMOylation (Boyes et al, 1998;Cantor and Orkin, 2002;Collavin et al, 2004;Yu et al, 2005;Hernandez-Hernandez et al, 2006;Lamonica et al, 2006;Zhao et al, 2006). Phosphorylation of GATA1 and its role in regulation of GATA1 function has been extensively adenovirus stock was a gift from F. Giordano (Yale University).…”
Section: Methodsmentioning
confidence: 99%